Context matters: Learner beliefs and interactional behaviors in an EFL vs. ESL context. (September 2022) - Sato, Masatoshi; Storch, Neomy
Researchers and teachers often invoke context to explain their particular research/teaching issues. However, definitions of context vary widely and the direct impact of the context is often unexplained. Based on research showing contextual differences in second language (L2) learner beliefs and interactional behaviors, the current project compared those factors in two distinct contexts: Chilean English as a foreign language (EFL) ( n = 19) and Australian English as a second language (ESL) ( n = 27) contexts. In this project, the learners completed a set of group discussion activities as part of their regular class work. They then completed a questionnaire pertaining to L2 motivation, perceptions of group work, and first language (L1) use. The group interaction data were analysed for: (1) the frequency of language-related episodes (LREs); (2) the initiator of LREs (self or other); and (3) L1 use for resolving LREs. The results showed that the EFL learners produced significantly more LREs. The EFL learners also used more L1 to resolve LREs. Factor analyses of the questionnaire data, conducted within- and across-contexts, showed notable differences in the two contexts as well. However, the findings of learner beliefs did not necessarily account for the differential classroom behaviors. We discuss our findings by reference to the socio-linguistic and socio-educational statuses of English in the two contexts as well as approaches to instruction which together shaped the learners' differential needs and purposes for learning the L2.